Diagonal technique of cross-country skiing on different slopes in a classical 10 km race - Hoga, K.; Sambongi, Y. (International Journal of Sport & Health Science, 2010)
The purpose of this study was to investigate the kinematic difference in the skiing motion of the diagonal technique between different slopes during classical style cross-country 10 km official race. Methods: Data were collected from two official men 10 km cross-country races of classical technique on the same 5 km circuit course. Skiers passing in the uphill sections of the course were videotaped with a VTR camera (60 Hz) positioned at 0.4 km point (3.8 degree slope) in one race, and at 1 km point (12.4 degree slope) in another race. To reconstruct the two dimensional coordinates of the motion of subjects, a two dimensional direct linear transformation technique was used. Seven skiers including national class junior and collegiate skiers of Japan were selected as subjects on each race. Results: The time from the instant of the heel contact on the ski to the instant of the ski detaching the snow on the moderate slope was almost same as that on the steep slope. However, the gliding length after heel contact on the ski on the moderate slope was larger than that on the steep slope. The length of ski gliding resulted in the large skiing speed on the moderate slope.